The Concept of Arc Elasticity of Demand: I - Allen, R. G. D. (Review of Economic Studies, 1934)
Journal Article The Concept of Arc Elasticity of Demand: I Get access R. G. D. Allen R. G. D. Allen London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 3, June 1934, Pages 226–229, https://doi.org/10.2307/2967486 Published: 01 June 1934